The Role of Religious Coping and Resilience in Individuals With Dissociative Identity Disorder. Issue 2 (October 2015) - Bell, Hope; Jacobson, Lamerial; Zeligman, Melissa; Fox, Jesse; Hundley, Gulnora
<x xml:space="preserve">Abstract</x> Survivors with dissociative identity disorder (DID) often report a history of traumatic events in their lives. Past studies indicated a link between trauma, resilience, and spiritual coping in both positive and negative aspects of a survivor's life. This article includes a review of existing literature salient to these constructs in relation to individuals with DID, as well as results from a study examining the relationships between these constructs and individuals with DID (N = 52). Implications are discussed based on the findings for counselors treating individuals with DID.